A note on spacelike submanifolds through light cones in Lorentzian space forms - Cánovas, Verónica L.; de la Fuente, Daniel; Palomo-Ruiz, Francisco José (Springer Nature, 2021)
We analyse the intrinsic and extrinsic geometry of spacelike submanifolds in light cones of de Sitter and anti-de Sitter spacetimes by means of an explicit correspondence with the spacelike submanifolds through the light cone in the Lorentz-Minkowski spacetime. In particular, a characterization of totally umbilical compact surfaces through light cones in de Sitter and anti-de Sitter is shown and we obtain an estimation of the  rst eigenvalue of the Laplace operator on a compact spacelike surface in a light cone
Keywords: Espacio y tiempo; De Sitter spacetime; Spacelike surface; Light cone; Anti-de Sitter spacetime